Analysis of building foundations on weak soils using FEM - Gąska, Bartłomiej; Nepelski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The reinforcement of soil with concrete columns, as well as pile foundations, is commonly used in building construction, particularly in cases where weak soils are present. This paper presents a comparative analysis of the foundation of an engineering structure using two methods: pile foundations and soil reinforcement with concrete columns. While both methods are similar in terms of execution, they differ in their working characteristics and calculation approaches. The structure analysed was a multi-family building consisting of two residential sections connected by an underground garage. Numerical analyses were conducted using the Finite Element Method (FEM). The load-bearing capacity of a single pile was calculated directly from the results of CPTU soundings using the LCPC method. The analysis led to the design of 1,096 concrete columns with a diameter of 300 mm and a total length of 7,485.5 metres, as well as 334 foundation piles with a diameter of 500 mm and a total length of 3,305.5 metres. The difference in concrete volume is approximately 120 m³ in favour of the columns, which constitutes nearly 20% of the total concrete volume. The columns were primarily designed in concrete, which results in additional steel savings, as all foundation piles would require reinforcement.